2004
DOI: 10.1079/bjn20041148
|View full text |Cite
|
Sign up to set email alerts
|

Maximum tolerable dose of red pepper decreases fat intake independently of spicy sensation in the mouth

Abstract: Dietary red pepper suppresses energy intake and modifies macronutrient intake. We have investigated whether a stimulus in the mouth and the sensation of spiciness are necessary for red pepper-induced changes in energy and macronutrient intake in human volunteers. In a preliminary test, sixteen Japanese male volunteers tasted samples of a soup with graded doses of red pepper in order to define a moderate and a maximum tolerable (strong) dose of red pepper. On the day of the experiment, a standardised breakfast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 31 publications
2
39
1
4
Order By: Relevance
“…Two studies have shown that the stimulating effect of CAP may occur both in the mouth and in the gastrointestinal regions by stimulating sensory pathways activating SNS in a dose-dependent manner. 11,12 However, in the present study we found no differences between the simple and controlled release versions of the compound on stimulation of thermogenesis, which contradicts our previous findings about the lack of thermogenic effect of the enterocoated version. 33 Even though there was a significant and maintained thermogenic effect of the compound after 8 weeks of supplementation, we failed to find a significant association between body fat loss and change in RMR.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Two studies have shown that the stimulating effect of CAP may occur both in the mouth and in the gastrointestinal regions by stimulating sensory pathways activating SNS in a dose-dependent manner. 11,12 However, in the present study we found no differences between the simple and controlled release versions of the compound on stimulation of thermogenesis, which contradicts our previous findings about the lack of thermogenic effect of the enterocoated version. 33 Even though there was a significant and maintained thermogenic effect of the compound after 8 weeks of supplementation, we failed to find a significant association between body fat loss and change in RMR.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been shown that CAP added to meals increases EE and fat oxidation 8,9 and decreases appetite 9,10 in humans, probably by stimulating sensory pathways in the mouth and in the gastrointestinal regions, leading to activation of SNS in a dose-dependent manner. 11,12 The effect of caffeine on appetite and thermogenesis is rather weak, and a supplement with caffeine 200 mg t.i.d. did not produce weight loss in obese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…One could speculate that the reduction in energy intake could partly be attributed to a reduced palatability of the diet when red pepper was added. However, two studies have found that the EI reducing effect of capsaicin may occur both in the mouth and in the gastrointestinal regions by stimulating sensory pathways activating SNS in a dosedependent manner (Westerterp-Plantega et al, 2004;Yoshioka et al, 2004). Therefore, the trend towards a reduced energy intake seen in the present study may lead to weight loss with higher doses taken over a longer period.…”
Section: Discussionmentioning
confidence: 54%
“…Human data suggest that adding chilli to a meal lowers total energy and macronutrient intake (Yoshioka et al, 1999;Yoshioka et al, 2001;Yoshioka et al, 2004;Belza and Jessen, 2005). Chilli also increases postprandial energy expenditure (EE) (Henry and Emery 1986;Yoshioka et al, 1995;Yoshioka et al, 1998), fat oxidation in women (Yoshioka et al, 1998) and carbohydrate oxidation in men (Yoshioka et al, 1995;Lim et al, 1997).…”
Section: Introductionmentioning
confidence: 99%